Shadow economy and economic growth: The role of institutional quality - Nguyen Thi My-Linh; Nga Phan Thi Hang; Chau Nguyen Xuan Bao (Contemporary Economics, 2024)
This paper focuses on analyzing the impact of the shadow economy on economic growth in ASEAN countries. In particular, the authors examine the role of institutional quality in the effects of the shadow economy on economic growth, which means that this study is different from previous studies. The data sample was collected in 10 ASEAN countries (Brunei Darussalam, Indonesia, Cambodia, Lao PDR, Myanmar, Malaysia, the Philippines, Singapore, Thailand, and Vietnam) from 2002 to 2019. Regarding the analytical method, the authors used a combination of threshold effects and the system - GMM (Generalized Method of Moments) method. The estimation results show a threshold value of institutional quality (λ = 21.23%). Accordingly, shadow economy negatively affects economic growth. This shows that improving institutional quality can help ASEAN countries limit the negative impact of the shadow economy on economic growth. In addition, the authors also find a positive effect of the control variables, such as government expenditure, foreign direct investment, and population growth, on economic growth. These research results are empirical evidence in ASEAN countries; thus, the findings in this study have important implications for ASEAN countries and other countries with similar characteristics.
Keywords: E02; O11; O47; P51; 330; ASEAN; economic growth; institutional quality; shadow economy; system - GMM